Editorial Vol.8 - Neupane, Khimananda (Vox Batauli, 2023)
Academic life stirs and gets renewed with every movement of creation that takes place with the rebirth of Vox Batauli: A Peer-Reviewed Journal. Its continuity since last seven years has proved its inexhaustible stamina and this time with its extra vigor of eighth volume it has successfully captured the momentum of Online-Intellectual Life in the form of NEPJOL. As the beauty of intellectual life lies in critical and creative thoughts and practices, the present volume shows the same with its creative writers and their different ways of dealing with various academic issues and interests. Of course, history of humanity cannot go ahead without critical and creative dialogue with new steps of time. In this regard, the present issue of Vox Batauli is bound to enrich and enhance humanity in true sense by the renewal of academic discourse. The journal has used both APA and MLA formats to accommodate the articles of different disciplines. We always regard the constructive suggestions as our guidelines. Finally, we would like to express our deep gratitude to all the contributors and reviewers for their active and sincere cooperation without which the journal would not come to this form.